Histórias contadas e vividas : memórias da Escola Normal Rural Murilo Braga de Itabaiana/Sergipe (1950/1972) - Costa, Silvânia Santana (2016)
The object of this study is the history of Murilo Braga Rural Normal School, located in the city of Itabaiana, State of Sergipe / Brazil. It was created in 1949 within the federal government project which aimed at the expansion of primary schools and rural normal schools, these in order to train teachers to work in rural areas. It would only be possible to promote the progress and development of the country if the most remote areas received education for life, a school that promoted the feeling of belonging and nationality, through agricultural, patriotic and hygienic values education. This mission of civilization through education had a responsible agent, the teacher, for that, it should be improved in rural normal school directed to training for rural areas. The governor of Sergipe, being ahead of the Department of Education, Acrísio Cruz began the expanding activities with the construction of Rural Normal School of Itabaiana and primary schools in all municipalities in the state. The physical structure of the school building of Murilo Braga Rural Normal School followed the architectural model of INEP, standard used in the construction of rural normal schools spread throughout the country. The project directed by Acrísio Cruz was widely praised and considered as pilot by Robert King Hall. In 1950, the school began the first class of junior high school and in 1969 it started to denominate Murilo Braga State School due to the creation of scientific course. The selected time frame for this study corresponds to the period from 1954 to 1972, in this, the teaching was regulated until 1960 by the Organic Law of the Normal Education, Decree Law No. 8530 of 1946 and from 1961 by Guidelines Law and Education Base (LDB No. 4024). The chosen time frame corresponded to the offer of the first group of normal course in 1954 and the completion of the last group in the life of the LDB of 1961. The classes after 1971 were regulated by the LDB No. 5692/71. The aim of this study is to analyze the process of teacher training of Murilo Braga. Within the purposes of the federal government, Murilo Braga Rural Normal School was created to train rural teachers, however, there wasn't the adequacy in the organization of normal and primary education of Sergipe, in order to meet the objectives of the implementation, and neither attracted a number of people to meet the demand for teachers in rural primary schools. The student teachers composed the teaching staff of Murilo Braga and primary schools in the city. The narrative is included in studies of the History of Education in the perspective of Cultural History, and oral, by allowing to study the various contexts in which historical subjects are inserted. The main concepts used were those of Civilization (ELIAS, 1993); Habitus (BOURDIEU, 1990); Representation (CHARTIER, 2009). The study contributes to the historiography of Sergipe Education, by discussing the history of primary teachers training from an inner educational institution, little explored by researchers of Sergipe education. A school that after 1970 was considered the reference to education in the state.